2015
DOI: 10.5751/es-07258-200143
|View full text |Cite
|
Sign up to set email alerts
|

Resilience assessment: a useful approach to navigate urban sustainability challenges

Abstract: ABSTRACT. Cities and towns have become increasingly interested in building resilience to cope with surprises, however, how to do this is often unclear. We evaluated the ability of the Resilience Assessment Workbook to help urban areas incorporate resilience thinking into their planning practice by exploring how a resilience assessment process complemented existing planning in the local government of Eskilstuna, Sweden. We conducted this evaluation using participant observation, semistructured interviews, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 23 publications
(37 reference statements)
0
48
0
2
Order By: Relevance
“…Although the Transition Movement aims to be inclusive, it has been criticized for lacking diversity (Smith 2011, Feola andNunes 2014) and for focusing more on raising awareness than experiential learning (Seyfang and Haxeltine 2012). Nevertheless, in our study we found that the Transition Movement approach complemented the Resilience Assessment's lack of guidance on process design (Sellberg et al 2015).…”
Section: Synergies In Fostering Complex Systems Understandingmentioning
confidence: 38%
See 2 more Smart Citations
“…Although the Transition Movement aims to be inclusive, it has been criticized for lacking diversity (Smith 2011, Feola andNunes 2014) and for focusing more on raising awareness than experiential learning (Seyfang and Haxeltine 2012). Nevertheless, in our study we found that the Transition Movement approach complemented the Resilience Assessment's lack of guidance on process design (Sellberg et al 2015).…”
Section: Synergies In Fostering Complex Systems Understandingmentioning
confidence: 38%
“…The last category was based on preliminary case study findings, which indicated that the Transition Movement approach focused more on practical tools, whereas the Resilience Assessment had a stronger theoretical foundation. This notion also aligned with another recent study of a resilience assessment process (Sellberg et al 2015). In order not to miss interesting findings, we also included interpretations of resilience in practice that emerged from the text analysis (2E in Table 1).…”
Section: Comparing Written Guidelines Through Qualitative Text Analysismentioning
confidence: 92%
See 1 more Smart Citation
“…It is suggested that regular and iterative assessment and the development of different future scenarios (that analyze future changes within short, medium, and long-term time horizons) can facilitate brainstorming on the complexities of urban system dynamics and, to some extent, prepare communities to deal with future uncertainties [4,58,59]. Such assessments and scenario-making processes may be resource intensive as they require regular updates of changing thresholds and baseline conditions [4,58]. Although regular assessment and scenario making can be somewhat effective, a shift from the "fail-safe" approach to the "safe-to-fail" approach requires acknowledging inadequacy and incompleteness of scientific knowledge for dealing with future changes and uncertainties.…”
Section: Discussionmentioning
confidence: 99%
“…There is now a growing recognition among planners that the "predict and prevent" approach to planning fails to appropriately accommodate modern complexities and persistent uncertainties [57]. It is suggested that regular and iterative assessment and the development of different future scenarios (that analyze future changes within short, medium, and long-term time horizons) can facilitate brainstorming on the complexities of urban system dynamics and, to some extent, prepare communities to deal with future uncertainties [4,58,59]. Such assessments and scenario-making processes may be resource intensive as they require regular updates of changing thresholds and baseline conditions [4,58].…”
Section: Discussionmentioning
confidence: 99%